A change in perspective: downhole cosmic-ray neutron sensing for the estimation of soil moisture - Rasche, Daniel; Weimar, Jannis; Schrön, Martin; Köhli, Markus; Morgner, Markus; Güntner, Andreas; Blume, Theresa (Hydrology and earth system sciences discussions, 2023)
Above-ground cosmic-ray neutron sensing (CRNS) allows for the non-invasive estimation of the field-scale soil moisture content in the upper decimetres of the soil. However, large parts of the deeper vadose zone remain outside of its observational window. Retrieving soil moisture information from these deeper layers requires extrapolation, modelling or other methods, all of which come with methodological challenges. Against this background, we investigate CRNS for downhole soil moisture measurements in deeper layers of the vadose zone. To render calibration with in situ soil moisture measurements unnecessary, we rescaled neutron intensities observed below the terrain surface with intensities measured above a waterbody.
Gesehen am 06.12.2023